Pituitary apoplexy: surgical or conservative? A meta-analytical insight - Xia, Kailai; Peng, Jihong; Zhou, Yunhao; Liu, Xiaoqing; Chen, Hongyu; Xu, Haiyang; Wang, Shuangji; Deng, Aini; Tang, Hua; Hu, Jinyang (Frontiers in Surgery, 2025)
ObjectivesThe challenge in treating pituitary apoplexy lies in choosing between conservative management and surgical intervention, with a current lack of high-level medical evidence to guide the selection of treatment options. This study compares the recovery rates of typical clinical manifestations following surgical and conservative treatments, aiming to provide evidence-based medical support for clinical treatment decisions.MethodsRelevant literature published between 1991 and 2024 was searched using PubMed, Embase, Cochrane Libraries, and CNKI. After a rigorous screening process to apply the inclusion and exclusion criteria, the primary clinical observation indicators were carefully extracted. The recovery rates of the main clinical observation indicators were evaluated using Reman v5.3. A fixed-effects model was employed to determine the merged odds ratio (OR) values, utilizing the Mantel-Haenszel estimation method. Publication bias was assessed using a funnel plot. Heterogeneity between studies was analyzed with the Cochran Q (Chi-square) test and I² statistics.ResultsThe meta-analysis results indicated that surgical treatment significantly improved recovery from ocular muscle paralysis compared to conservative treatment (OR: 0.31; 95% CI 0.10–0.92; p = 0.04). However, no statistically significant differences were observed in postoperative recovery of visual acuity (OR: 1.15; 95% CI 0.54–2.44; p = 0.72), visual field recovery (OR: 1.48; 95% CI 0.77–2.82; p = 0.24), or pituitary endocrine function (OR: 0.67; 95% CI 0.27–1.67; p = 0.38).ConclusionOur research findings suggest that patients with pituitary apoplexy presenting with ocular palsy may benefit more from surgical treatment.